Analisis Durasi Tidur, Kualitas Tidur, dan Kesehatan Fisik Mahasiswa Bioteknologi Universitas Muhammadiyah Bandung pada Berbagai Semester: Studi Kasus Tanpa Hubungan Signifikan - Nisa Ihsani; Siti Nurbaeti; Neva Afifah Putri Suharja; Viga Indra Kusumawati; Rizki Pajar Nugraha (Jurnal Biodiversitas dan Bioteknologi, 2024)
College students usually experience difficulties and sleep disorders, which would harm their health and can affect their academic performance. This study was conducted to analyze the correlation between sleep duration, sleep quality, and physical health of Biotechnology students at Universitas Muhammadiyah Bandung. The research was carried out using questionnaires. The questionnaire analysis result showed that the average sleep duration of students was 2-4 hours. However, there was no correlation between sleep duration and physical health (p>0.05), as well as between sleep quality and physical health (p>0.05) at every semester levels.